Nível tecnológico e competitividade da produção de mel de abelha (Apis mellifera) no Ceará - Freitas, Débora Gaspar Feitosa (2003)
The present study aimed to analyze the beekeeping in the State of Ceará focusing the honey production in the main municipal districts producing of the State, precisely making an analysis of the technological level employed in the production, as well as evaluating the profitability of the activity and the competitiveness in terms of efficiency of the producers, and finally the relationship of technological level and competitiveness. The research took place through collection of primary data through direct interviews with the producers in the municipal districts of Mombaça, Pacajús e Chorozinho – State of Ceará, during October 2002. To evaluate technological level, the honey production system was separated in five technologies: equipments, management, harvest, after-harvest and administration; then technological indexes were developed separately for each technology and for their group, based on the respective recommended technology, where the more close of the recommended technology, higher is the value of this index and, therefore better the technological level. The evaluation of the profitability was made by using the methodology of the Integrated System of Agricultural Costs - CUSTAGRI, and for competitiveness analysis it was used the efficiency indicators as prices and costs, and profitability indicators as operational profit and profitability index. To verify the relationship between the technological level and the competitiveness a simple regression it was used by the method of the Ordinary Square Minimum - MQO, where the competitiveness was analyzed as variable dependent of the technological level. The main obtained results shows that the technological level of honey production is considered good, and the technology of after-harvest presents better indexes, while in the technology of administration, was found the lowest indexes. Concerning to the profitability, the honey production is a profitable activity, involving low costs and could arrive high profitability indexes. The technological levels influence the competitiveness positively.